Development of the Dribble Exercise Model in Soccer of Fpok Student in IKIP Mataram - Syah, Herman; Tangkudung, James; Hanif, Ahmad Sofyan (International Journal for Educational and Vocational Studies, 2019)
The purpose of this study was to develop a dribble training model for soccer games of fool students in IKIP Mataram. The method used in this study is the research methodology and development of Borg and Gall, which consists of ten stages. The final results of this research and development are written in a handbook on dribble training models for soccer games for those that have been evaluated by experts, trial and revision, and their effectiveness has been tested. The instruments used in this development research were questionnaires and the Instrument Test dribble. The design of this study uses research & development (R & D) research methods from Borg and Gall in the form of qualitative and quantitative approaches used to reveal the second objective, with a pre-experimental research design in the form of the one-group pretest-posttest design that looks for significant differences in the exercise model before and after being given a training model. Where the analysis of data research uses the t-test with a significance level of 0.05, Therefore, the effectiveness of the development of the model develops a model of dribble training on the basis of improving skills in dribble giving a reference so that this training model can be used to do variation training in implementing football dribble on students of Fool in IKIP Mataram.